Resúmenes: Bragado Mateos, Maqueda Abreu, Vilchez Díaz, Gómez Rivas, Carrasco Martínez, Martínez Gil, Vázquez González, Martínez Vega, Collantes Fernández, Ceñal Lorente, Sabater Galindo, Simorte, Herrero Fernández-Quesada, Sánchez González - autor, Sin (Cuadernos de Historia Moderna, 1991)
Sin resumen